Prohibitin 2 Is an Inner Mitochondrial Membrane Mitophagy Receptor - Wei, Yongjie; Chiang, Wei-Chung; Sumpter, Jr, Rhea; Mishra, Prashant; Levine, Beth (Cell, 2017)
The removal of unwanted or damaged mitochondria by autophagy, a process called mitophagy, is essential for key events in development, cellular homeostasis, tumor suppression, and prevention of neurodegeneration and aging. However, the precise mechanisms of mitophagy remain uncertain. Here, we identify the inner mitochondrial membrane protein, prohibitin 2 (PHB2), as a crucial mitophagy receptor involved in targeting mitochondria for autophagic degradation. PHB2 binds the autophagosomal membrane-associated protein LC3 through an LC3-interaction region (LIR) domain upon mitochondrial depolarization and proteasome-dependent outer membrane rupture. PHB2 is required for Parkin-induced mitophagy in mammalian cells and for the clearance of paternal mitochondria after embryonic fertilization in C. elegans. Our findings pinpoint a conserved mechanism of eukaryotic mitophagy and demonstrate a function of prohibitin 2 that may underlie its roles in physiology, aging, and disease.